Collaboration between Teachers and Parents in Accommodating the Learning Needs of Students with Speech Delays at Karangan 1 State Kindergarten - Nuryanti Nuryanti; Bayu Pamungkas (International Journal of Educational Research, 2025)
This research aims to describe the collaboration between teachers and parents in meeting the learning needs of students with speech delays at Karangan 1 State Kindergarten. It focuses on examining strategies applied to overcome learning barriers while identifying both supporting and inhibiting factors in the practice of inclusive education. The central concern is how interaction and cooperation between home and school create a consistent, responsive learning environment for children with special needs. Employing a qualitative descriptive approach with a case study design, the study was conducted for one trimester of the 2024/2025 academic year. Research participants included classroom teachers, parents of children with speech delays, and relevant documentation related to inclusive education policies. Data were collected through in-depth interviews, observations, and document studies, with interview guides and observation sheets as instruments. Validity was ensured through triangulation and member checking, while data analysis followed the Miles and Huberman model: reduction, display, and conclusion drawing. Findings reveal active teacher-parent collaboration characterized by regular communication, joint discussion of learning strategies, and parental involvement in school programs. Supporting factors include open communication, shared commitment, and policy support, while obstacles involve limited teacher training, insufficient learning media, and lack of access to speech therapy specialists. The study highlights the need for continuous inclusive training, adequate learning resources, and regular communication forums to optimize education for children with speech delays.